Effects of upper-body and lower-body conditioning activities on postactivation performance enhancement during sprinting and jumping tasks in female soccer players - Santos da Silva, V.; Nakamura, F. Y.; Gantois, P.; Nogueira Gouveia, J. N.; Peña, J.; Beato, M.; Abade, E. (The Journal of Strength and Conditioning Research, 2024)
This study aimed to investigate the postactivation performance enhancement (PAPE) effects of "specific" (half-back squat) and "nonspecific" (bench press) conditioning activities on sprinting and jumping performances in female soccer players. Fourteen players (mean ± SD: age = 22.3 ± 4.0 years; body mass = 60.2 ± 7.8 kg; height = 164.1 ± 4.2 cm) competing at national level (first League) participated in this within-subject crossover study. The players performed a warm-up protocol including 3 sets of 3 repetitions of half-back-squat or bench press exercises at 90% 1RM or a warm-up protocol without lifting weights (i.e., control condition). Forty-meter shuttle sprints (20 + 20 m with change of direction [COD-180°]), countermovement jump (CMJ), and horizontal jump (HJ) performances were recorded 6 minutes after the conditioning activities protocols or the control condition. Nonsignificant large positive effects were found for the HJ after the half-back-squat (ES = 1.68; p > 0.05) and bench press (ES = 1.68; p > 0.05) protocols. Although nonsignificant, HJ changes (? = 0.07 m) were greater than the smallest worthwhile change (0.02 m) and standard error of measurement (0.03 m) after both conditioning activities. Moreover, no significant changes were found for sprint and CMJ performance after neither half-back-squat nor bench press protocols (p > 0.05). In conclusion, both specific and nonspecific conditioning activities using heavy loads (i.e., 90% 1RM) may be suitable to enhance individual HJ. Finally, both conditioning activities are potentially ineffective for increasing sprint and CMJ performance in the context of this study.